You're fifty - now what ? : investing for the second half of your life - Schwab, Charles R. (Crown Business New YorkUS, 2001)
Provides the age 50+ American population with a six-point investing strategy that takes into account current changes, and promises financial security during retirement. Discusses topics including: when/how to choose a financial advisor; adequate \n insurance coverage; and bequeathing property. Advocates charitable giving of money/ appreciated assets/ time/ talent/ expertise, to deserving organizations. Provides a glossary; and includes worksheets, tables, questionnaires, and further information in the appendix.